MANGLAYDAGI DOG (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the story “Dog” by the writer Khaliyor Safarov. Some symbolic details in it are commented on, as well as a comparative analysis of image and dialogue motifs with other works.